2020
DOI: 10.3390/foods9060725
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Production System and Sex on the Sensory Quality Characteristics of Dorper Lamb

Abstract: The effect of production systems on the sensory quality characteristics of Dorper lambs was investigated. Sixty lambs (ewes, rams, castrates) were allocated into two production groups (feedlot or free-range) at weaning with equal numbers of each sex represented in each group. The lambs were fed for five (slaughter group 1) or six (slaughter group 2) weeks. Feedlot lambs were fed a commercial pelleted diet while free-range lambs utilized natural shrub pastures. Samples of the Longissimus thoracis muscle were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Fatty acid composition influences the nutritive value and organoleptic traits of meat including tenderness, flavor, and juiciness [20]. The fatty acid content of meat can be affected by the animal production system [21,22], breed or genotype [23,24], gender [25], age at slaughter [26], liveweight [27], level of fatness [20], type of muscle and feed. In lamb [28], cattle, swine, and poultry [29], it has been suggested that dietary manipulation can be utilized to improve the fatty acid content and nutritional value of meat that more closely meets nutritional guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid composition influences the nutritive value and organoleptic traits of meat including tenderness, flavor, and juiciness [20]. The fatty acid content of meat can be affected by the animal production system [21,22], breed or genotype [23,24], gender [25], age at slaughter [26], liveweight [27], level of fatness [20], type of muscle and feed. In lamb [28], cattle, swine, and poultry [29], it has been suggested that dietary manipulation can be utilized to improve the fatty acid content and nutritional value of meat that more closely meets nutritional guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Research investigations of perceived sheepmeat eating quality sensory scores [ 28 ] and demographic influences [ 29 ] on Australian, American and Chinese consumers demonstrated a consistent consumer response to production factors of muscle type, sire, age, and sex. Evidence in the published literature [ 30 ] indicates that meat eating quality and fatty acid (FA) composition of lipids in tandem with variable fat deposition at the attainment of maturity, vary in the muscles of sheep due to differences in breed [ 31 , 32 , 33 , 34 ], physiological status, breeding systems [ 35 ], grass-fed versus concentrate feeding [ 36 , 37 ], and sex [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of water-holding capacity has been established. It was not only associated with juiciness [52] and tenderness [53], but also with water loss and nutrient loss. Therefore, the level of pressing loss and cooking loss reflected the quality of the meat to a certain extent.…”
Section: Discussionmentioning
confidence: 98%